A novel maltoheptaose-based sugar ester having excellent emulsifying properties and optimization of its lipase-catalyzed synthesis. (1st August 2021) - Nguyen, Phu Cuong; Nguyen, My Tuyen Thi; Kim, Jae-Han; Hong, Soon-Taek; Kim, Hye-Lynn; Park, Jong-Tae
Highlights: Enzymatic synthesis of G7-PA using CCD of RSM was successfully optimized. A high conversion yield of G7-PA (92.75%) was obtained at the optimized condition. G7-PA emulsion was more stable than S-PA emulsion at low emulsifier concentration. G7-PA emulsion was stable at pH 3, but S-PA emulsion showed complete phase separation. Abstract: A novel maltoheptaose-palmitate ester (G7-PA) was synthesized and investigated for emulsion properties. First of all, the optimal conditions for lipase-catalyzed G7-PA synthesis, which were 0.2 of the G7/PA molar ratio, 33.5 U of immobilized CALB per 1 g of PA in 10% DMSO, were determined by response surface methodology. G7-PA was compared with the commercial sucrose-PA (S-PA) in terms of emulsion-forming ability and stability at extreme conditions. At the 0.1% surfactant concentration, G7-PA emulsion exhibited a droplet distribution similar to the 0.2% surfactant condition, while S-PA emulsion was quickly destabilized. G7-PA showed better emulsifying properties than the S-PA at the acidic condition (pH 3). Flocculation and phase separation was observed at the S-PA emulsion, but the G7-PA emulsion was stable for 7-day. In thermostability tests, G7-PA and S-PA both were stable up to the boiling temperature. Conclusively, G7-PA exhibits excellent properties as a biosurfactant in O/W emulsion compared with S-PA.